Crystallinity of hydroxyapatite drives myofibroblastic activation and calcification in aortic valves. (15th April 2018) - Richards, Jennifer M.; Kunitake, Jennie A.M.R.; Hunt, Heather B.; Wnorowski, Alexa N.; Lin, Debra W.; Boskey, Adele L.; Donnelly, Eve; Estroff, Lara A.; Butcher, Jonathan T.
Graphical abstract: Abstract: Calcific aortic valve disease (CAVD) is an inexorably degenerative pathology characterized by progressive calcific lesion formation on the valve leaflets. The interaction of valvular cells in advanced lesion environments is not well understood yet highly relevant as clinically detectable CAVD exhibits calcifications composed of non-stoichiometric hydroxyapatite (HA). In this study, Fourier transform infrared spectroscopic imaging was used to spatially analyze mineral properties as a function of disease progression. Crystallinity (size and perfection) increased with increased valve calcification. To study the relationship between crystallinity and cellular behavior in CAVD, valve cells were seeded into 3D mineral-rich collagen gels containing synthetic HA particles, which had varying crystallinities. Lower crystallinity HA drove myofibroblastic activation in both valve interstitial and endothelial cells, as well as osteoblastic differentiation in interstitial cells. Additionally, calcium accumulation within gels depended on crystallinity, and apoptosis was insufficient to explain differences in HA-driven cellular activity. The protective nature of endothelial cells against interstitial cell activation and calcium accumulation was completely inhibited in the presence of less crystalline HA particles. Elucidating valve cellular behavior post-calcification is of vital importance to better predict and treat clinical pathogenesis, and mineral-containing hydrogel models provide a unique 3D platform to evaluate valve cell responses to a later stage of valve disease. Statement of Significance: We implement a 3D in vitro platform with embedded hydroxyapatite (HA) nanoparticles to investigate the interaction between valve interstitial cells, valve endothelial cells, and a mineral-rich extracellular environment. HA nanoparticles were synthesized based on analysis of the mineral properties of calcific regions of diseased human aortic valves. Our findings indicate that crystallinity of HA drives activation and differentiation in interstitial and endothelial cells. We also show that a mineralized environment blocks endothelial protection against interstitial cell calcification. Our HA-containing hydrogel model provides a unique 3D platform to evaluate valve cell responses to a mineralized ECM. This study additionally lays the groundwork to capture the diversity of mineral properties in calcified valves, and link these properties to progression of the disease.